Granul Ekstrak Kayu Secang (Caesalpinia sappan L.) dan Rimpang Temu Mangga (Curcuma mangga Val & Zijp.) sebagai Antibakteri - Nelly Uyo; Swasono R. Tamat; Kosasih Kosasih (Jurusan Biologi FMIPA Universitas Cenderawasih, 2018)
Kayu secang (Caesalpinia sappan) and rimpang temu mangga (Curcuma mangga) are medicinal plants that are efficacious for diarrhea due to bacterial infection. Kayu secang and Rimpang temu mangga contain secondary metabolite compounds capable of providing antibacterial activity, ie flavonoids. This study aimed to obtain the granule as supplies, which contain a combination of kayu secang and rimpang temu mangga with good quality, it is favored by consumers and has high antibacterial activity. Both powdered simplisia powder was kinetic with ethanol 70 % and dried by freeze drying method. Both powder extract tested the quality of raw material and test of antibacterial activity against bacteria Escherichia coli, Salmonella sp and Shigella sp. Both powder extracts were made granular preparations with the addition of excipients (Handbook of Pharmaceutical Excipients). The granule preparations were tested for granule quality standards and preferred levels and antibacterial activity. Data were analyzed statistically with one way ANOVA method (p= 0.05). Rimpang temu mangga extract powder added maltodextrin did not provide antibacterial activity. The granule extract of Kayu secang extract of formula 1 (F1) meets the requirements of granule quality standard, preferably consumer and has high antibacterial activity, i.e 18.7 mm against E. coli bacteria, 28.3 against Salmonella sp bacteria and 30.5 against Shigella sp bacteria. Key words: Secang, C. sappan, temu mangga, extract, granule, antibacterial